Article RETRACTED due to malpractice Effect of a Physical Activity-Based Intervention Package on Labor Pain: A Randomized Controlled Trial - Sri Utami Subagio; Nurseha; Marthia Ikhlasiah (Retos, 2026)
Background: Labor pain may affect maternal comfort and the progress of childbirth. Non-pharmacological interventions such as breathing relaxation exercise and pelvic rocking exercise are considered safe and practical methods to reduce labor pain. Objective: This study aimed to analyze the effect of breathing relaxation exercise and pelvic rocking exercise on labor pain among women during the active phase of the first stage of labor. Methods: This randomized controlled trial was conducted at Pamarayan Primary Health Center from August to December 2025. A total of 80 respondents were randomly assigned to intervention and control groups, with 40 participants in each group. The intervention group received breathing relaxation exercises and pelvic rocking exercises, while the control group received standard maternal care. Labor pain intensity was measured using the Visual Analog Scale (VAS). Data were analyzed using wilcoxon test, the Mann-Whitney test, and ANCOVA with a significance level of p<0.05 using IBM SPSS Statistics version 26.0. Results: The mean labor pain score in the intervention group significantly decreased from 7.68 ± 0.92 before intervention to 4.95 ± 1.01 after intervention (p<0.001), whereas the control group showed a smaller reduction from 7.55 ± 0.88 to 6.92 ± 1.07 (p=0.041). Independent t-test analysis showed a significant difference in post-intervention pain scores between the intervention and control groups with a mean difference of -1.97 (95% CI: -2.43 – -1.51; p<0.001). Multivariate analysis showed that the intervention remained the strongest factor associated with reduced labor pain after controlling for maternal age, education level, parity, anxiety level, family support, and duration of labor (B=-1.842; 95% CI: -2.301 – -1.383; p<0.001). Conclusion: Breathing relaxation exercise and pelvic rocking exercise were effective in reducing labor pain among women during the active phase of the first stage of labor. The intervention may be used as a safe non-pharmacological approach in primary maternal healthcare services.